Assessment of the Mental Health Continuum in a Sample of Argentinean Adults - Castro Solano, Alejandro (2017)
The aims of this study are 1) to evaluate the mental health continuum and the dual-continua model classifications in a sample of Argentinean adults; and 2) to compare the mental health prevalence according to demographic variables and the presence of significant psychiatric symptoms. The sample included 627 adults (49.8% males and 50.2% females). The mean age of participants was 40.62 years old. The Symptom Checklist-90-Revised and the Mental Health Continuum-Short Form were used in the study. A high proportion of adults had flourishing mental health (39.7%), and only a minority had languishing mental health (5.7%). Higher mental health was related only to having income. Having any mental disorder significantly decreased mental health status, and individuals were more languishing and less flourishing in all mental disorder categories. Findings showed Argentinean adults to have very good mental health.